RANBP2 mutation and acute necrotizing encephalopathy: 2 cases and a literature review of the expanding clinico-radiological phenotype. (March 2015) - Singh, Rahul R.; Sedani, Sagar; Lim, Ming; Wassmer, Evangeline; Absoud, Michael
Abstract: Background: Acute necrotising encephalopathy (ANE) is a rapidly progressive encephalopathy associated with acute viral illness. A missense mutation in nuclear pore gene RANBP2 has been identified as a major cause of familial and recurrent ANE, which is now termed as ANE1. First presentation of ANE can mimic an acute disseminated encephalomyelitis (ADEM), although ANE presents in a slightly younger age group. Identification of this disorder at radiological study is the most important determinant of the outcome. ANE1 is inherited as autosomal dominant, but shows incomplete penetrance. Methods: We report two female children who presented with atypical clinical presentation (afebrile) and atypical radiological presentation (lack of bilateral thalamic involvement), not fitting into the original diagnostic criteria for ANE1. Both received steroid therapy for a presumed diagnosis of ADEM and made good clinical recovery. We also reviewed the available literature on ANE1, including the clinical profile, MRI brain descriptions, CSF characteristics and common mutations. Results: A total of 59 patients are reported in patients with ANE1 were identified, the incidence of ANE was higher in younger age group (<4 yrs) as compared to ADEM 5.3 yrs (3.6–7). Male and female were equally affected. High CSF protein (>0.45 g/l) was reported in 44/47 (94%) in absence CSF pleocytosis (Cells > 5 × 10 6 /L). Neuroimaging findings showed multifocal involvement across different studies, and bilateral thalamic involvement was seen in 77% of patients. Conclusion: Based on the literature review of ANE1 with RANBP2 mutation, we propose a threshold for RANBP2 mutation testing.